PEMANFAATAN MEDIA AJAR BERBASIS VIDEO TUTORIAL TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN INFORMATIKA DI KELAS X SMK S 10 KOTA BENGKULU - Putra, Apriansyah; Selviani, Diah; Fitria, Yenni (Journal Of Dehasen Educational Review, 2023)
This study aims (1) to find out how the Utilization of Video Tutorial-Based Teaching Media Against Students’ Learning Outcomes in Informatics Subject in Class X at SMK S 10, Bengkulu City. (2) to find out how the use of video tutorial-based teaching media on students’ learning outcomes in informatics subject in class X at SMK S 10, Bengkulu City. The method used in this study is a qualitative research method, with data collection techniques in the form of observation, tests and questionnaires. The samples in this study were the students of class X Access Network Engineering. The results of this study are based on the results of observations, questionnaires, and tests conducted, that the use of tutorial-based video learning media has a positive impact on learning informatics for class X students. Teachers who use this media are able to manage classes better and pay attention to students who not focus while watching the learning video. The majority of students, namely 98% (41% strongly agreed and 57% agreed), gave a positive response to the use of video tutorial-based teaching media. The enthusiasm of students in participating in the learning process with this media was also a positive indicator. Student learning outcomes also showed the success of using video tutorial-based teaching media. The range of scores obtained by students ranges from 76 to 100, with the lowest score exceeding the Minimum Completeness Criteria (KKM) set, namely 75. This shows that the students are able to achieve the standards set in informatics subjects with the help of video-based teaching media tutorials.